2015
DOI: 10.1038/npp.2015.171
|View full text |Cite
|
Sign up to set email alerts
|

Stress Effects on Neuronal Structure: Hippocampus, Amygdala, and Prefrontal Cortex

Abstract: The hippocampus provided the gateway into much of what we have learned about stress and brain structural and functional plasticity, and this initial focus has expanded to other interconnected brain regions, such as the amygdala and prefrontal cortex. Starting with the discovery of adrenal steroid, and later, estrogen receptors in the hippocampal formation, and subsequent discovery of dendritic and spine synapse remodeling and neurogenesis in the dentate gyrus, mechanistic studies have revealed both genomic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
769
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,073 publications
(859 citation statements)
references
References 216 publications
(247 reference statements)
29
769
1
8
Order By: Relevance
“…Though we did not test the effect of chronic stress exposure in other developmental periods, our findings corroborate other studies indicating that the prefrontal cortex is particularly sensitive to stress exposure during infancy and adolescence [60,61]. Chronic stress can be induced in the laboratory by continuously submitting animals to stressful situations, such as physical immobilization, and observing the effects on brain and/or behavior.…”
Section: Discussionsupporting
confidence: 81%
“…Though we did not test the effect of chronic stress exposure in other developmental periods, our findings corroborate other studies indicating that the prefrontal cortex is particularly sensitive to stress exposure during infancy and adolescence [60,61]. Chronic stress can be induced in the laboratory by continuously submitting animals to stressful situations, such as physical immobilization, and observing the effects on brain and/or behavior.…”
Section: Discussionsupporting
confidence: 81%
“…Of note, mGluR2/3 antagonists have demonstrated ketamine-like antidepressant effects (Duman, 2014;McEwen et al, 2016). Finally, we propose that the decrease in intrasynaptic glutamate also leads to further atrophy and loss of intrasynaptic NMDA receptors.…”
Section: Conceptual Convergence: a Working Modelmentioning
confidence: 99%
“…Increased extrasynaptic glutamate can also bind to presynaptic neuronal metabotropic mGluR2/3 autoreceptors inhibiting glutamate release leading to chronic reductions in intrasynaptic glutamate, loss of excitatory synaptic activity, and ultimately result in synaptic loss (Duman, 2014;Duman et al, 2016;McEwen et al, 2016). Of note, mGluR2/3 antagonists have demonstrated ketamine-like antidepressant effects (Duman, 2014;McEwen et al, 2016).…”
Section: Conceptual Convergence: a Working Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are underlying changes that can be seen at the level of gene expression and epigenetic regulation that indicate that the brain is continually changing (9, 10). Epigenetic modifications, such as acetylation of histones, have also been involved in the consolidation of contextual memories that allow the brain to respond and adapt to changes in the environment (11).Among the large number of mediators of brain structural and functional plasticity, the glutamatergic system and BDNF play a key role in mediating the effects of stress on both cognition and psychopathology (1,(12)(13)(14)(15). Animal models have shown that chronic stress effects on dendritic remodeling are blocked by blocking NMDA receptors (1,16) and that adrenalectomy attenuates the acute stress-induced elevations of extracellular glutamate levels in the hippocampus (1, 17).…”
mentioning
confidence: 99%